Development of Coated Graphite and Wire Electrodes for Methyldopa Determination in Pharmaceutical and Pure Products - Amer, Hasan; Salih Hassan, Omar (University of Thi-Qar Journal of Science, 2025)
Two designs of methyldopa-selective electrodes were compared: electrode A, which was copper-coated and electrode B, which was a coated graphite electrode (CGE) based on the ion-exchanger complex of methyldopa- Phosphotungstic acid (MeD-PTA). With a detection limit of 3.2×10-6 M and a Nernstian slope of 54.97 mV/decade, Electrode A exhibits a wide linear dynamic range to detected a concentration of MeD which was equals to 5.1×10-6 - 1.0×10-2 M.  The limit of detection of 1.4×10-6 M and a Nernstian slope of 57.12 mV/decade, Electrode B showed linearity over the range of concentrations of 4.0×10-8 to 1.0×10-2 .Methyldopa (MeD) exhibited a good selectivity over a wide range of inorganic cations, starch, and glucose, according to selectivity coefficients calculated using the separate solution method (SSM). The MeD in tablet samples was ascertained using the calibration curve method and potentiometric measurement. using the suggested sensors, excellent percentage recovery was one of the outcomes, which were adequate and occasionally better than those from other standard assay procedures. Because of its appealing qualities, the CGE is more suited for commercialization.